Evaluation of Argovit silver nanoparticles as antimicrobial treatment for diabetic foot ulcers on mexican population at Rosarito general hospital; 2nd International Symposium on Nanoscience and Nanomaterials SINN, Ensenada, Baja California, Mexico, March 4-8, 2012, CNyN-UNAM, "Welcome to the Bionanotechnology Group" - Almanza H.; Garcia L.; Vera C.; Vega R.; Chavez J.; Almonaci C.; Bogdanchikova N.; Burmistrov V.; Pestryakov A. N. Aleksey Nikolaevich (2013, 2013)
В фонде НТБ ТПУ отсутствует